2014
DOI: 10.1007/s00439-014-1468-7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothesis-independent pathway analysis implicates GABA and Acetyl-CoA metabolism in primary open-angle glaucoma and normal-pressure glaucoma

Abstract: Primary open-angle glaucoma (POAG) is a leading cause of blindness worldwide. Using genome-wide association single-nucleotide polymorphism data from the Glaucoma Genes and Environment study and National Eye Institute Glaucoma Human Genetics Collaboration comprising 3,108 cases and 3,430 controls, we assessed biologic pathways as annotated in the KEGG database for association with risk of POAG. After correction for genic overlap among pathways, we found 4 pathways, butanoate metabolism (hsa00650), hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 48 publications
5
27
0
Order By: Relevance
“…The intronic variant rs62391530 showed the strongest relation to POAG with a nominal p-value of 0.02 and an effect size of −0.16. Even though ALDH7A1 variants did not reach the genome-wide significance threshold of 5 × 10 −8 , this gene is part of the KEGG “butanoate metabolic pathway”, which was previously identified to be associated with both POAG and NTG (Bailey et al, 2014). …”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…The intronic variant rs62391530 showed the strongest relation to POAG with a nominal p-value of 0.02 and an effect size of −0.16. Even though ALDH7A1 variants did not reach the genome-wide significance threshold of 5 × 10 −8 , this gene is part of the KEGG “butanoate metabolic pathway”, which was previously identified to be associated with both POAG and NTG (Bailey et al, 2014). …”
Section: Resultsmentioning
confidence: 87%
“…While GWAS have identified many genes associated with glaucoma risk, a recent analysis (Bailey et al, 2014) used a randomized analysis to take the single gene data and assign associated molecular pathways. One pathway involved butanoate metabolism (KEGG pathway hsa00650; see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We executed PARIS on GWAS results from 480 k SNPs evaluated by the NEIGHBOR consortium (Bailey et al, 2014;Wiggs et al, 2012). Comparing results from a prior version of PARIS (1.1.3) to this new version (2.4), results are highly correlated (Fig.…”
Section: Performance Validationmentioning
confidence: 99%
“…1B and C) for the 199 overlapping KEGG pathways, using gene boundary thresholds of 0 and 50 kb. To provide a comprehensive and unbiased comparison, we utilized the database and pathway definition files that were previously utilized with version 1.1.3 of PARIS (Bailey et al, 2014). Pathway P-values were highly correlated, as indicated in Figure 1B and C. Further, we evaluated the number of pathways attaining P < 0.05 ( Table 1) and found that with both the 0 and 50 kb gene boundary extension options, the same pathways achieved this significance threshold, except in one case, where a pathway was P < 0.05 in the prior version of PARIS and P 0.05 in the updated version due to difference in random number generation between the two versions.…”
Section: Performance Validationmentioning
confidence: 99%